2022
DOI: 10.3389/fpsyg.2022.938090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Music Education on Mental Health of Higher Education Students: Moderating Role of Emotional Intelligence

Abstract: Music education is one of human kind most universal forms of expression and communication, and it can be found in the daily lives of people of all ages and cultures all over the world. As university life is a time when students are exposed to a great deal of stress, it can have a negative impact on their mental health. Therefore, it is critical to intervene at this stage in their life so that they are prepared to deal with the pressures they will face in the future. The aim of this study was to see how music e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…47 High emotional intelligence could significantly alleviate the anxiety, maintaining mental health for students during the pandemic. 12 , 13 Moreover, it has been shown that psychological support might mitigate the effect of COVID-19-caused stress in university students in Bangladesh during COVID-19 pandemic 20 and that individuals with more psychological support had better mental health status. 19 In consistence with this principle, our study showed that at the same level of emotional intelligence, college students with a high psychological capital score had better self-rated health state than those with a low one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…47 High emotional intelligence could significantly alleviate the anxiety, maintaining mental health for students during the pandemic. 12 , 13 Moreover, it has been shown that psychological support might mitigate the effect of COVID-19-caused stress in university students in Bangladesh during COVID-19 pandemic 20 and that individuals with more psychological support had better mental health status. 19 In consistence with this principle, our study showed that at the same level of emotional intelligence, college students with a high psychological capital score had better self-rated health state than those with a low one.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Wang et al reported that professional students who had a high level of emotional intelligence could keep mental health better during the pandemic. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Hafsa and colleagues also observed a positive correlation between emotional intelligence and loneliness in adolescents 47 . High emotional intelligence could signi cantly alleviate the anxiety, maintaining mental health for student during the pandemic 12,13 . Moreover, it has been shown that psychological support might mitigate the effect of COVID-19-caused stress in university students in Bangladesh during COVID-19 pandemic 20 , and that individuals with more psychological support had better mental health status 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang and colleagues reported that professional students who had a high level of emotional intelligence could keep mental health better during the pandemic 13 .…”
Section: Introductionmentioning
confidence: 99%